094 The adult phenotypes of paediatric-onset genetic epilepsies. Issue 12 (14th November 2019) - Lewis-Smith, David; Craig, Donald; Thomas, Rhys
Abstract : Genetic discovery in epilepsies has focussed on cohorts of children who typically have severe and intractable seizures. Now that genetic testing for adults with epilepsy has entered routine clinical practice, we are able to learn about the developmental trajectory of these epilepsies. Undiagnosed patients with epilepsy and intellectual disability were offered gene panel testing in an NHS epilepsy clinic. We present the clinical features of eight adults found to carry variants in paediatric epilepsy genes during re-investigation. All are amongst the oldest cases described. In six cases (CHD2, CNTNAP2, KCN1A, KCNT1, SCN2A, SCN8A) the onset was typical of published cases and we describe the evolution of their syndromes into adulthood including EEG and imaging. In two (SMC1A, NEXMIF) the onset was significantly later than published cases and we hypothesise that the phenotypic spectrum is broader than first thought for these disorders. Rare variants in genes associated with developmental and epileptic encephalopathies occur in adults with epilepsy. Stratifying patients with regards to syndromic diagnosis will facilitate more precise personalised prognostication and ultimately molecularly stratified treatment strategies. To maximise this potential it will become more important over the coming years for adult neurologists to undertake and understand genetic testing and collaborate with longitudinal observational studies of cohorts defined by molecular features.